Potential efficacy of crizanlizumab in treating priapism in sickle cell disease: A case report - Mohammed Abdulgayoom (14777791) (2024)
Key Clinical Message This report documents the treatment of a 41‐year‐old male with sickle cell disease (SCD) and repeated stuttering priapism using crizanlizumab, which alleviated the priapism but induced a significant vaso‐occlusive crisis during the second infusion. Encouragingly, no subsequent vaso‐occlusive crises occurred. However, the potential for infusion‐related adverse events warrants close supervision. Further research is necessary to explore its full benefits on priapism management. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.8585